Senior High School Students: Their Fitness Level and Their Academic Performance - Lacasan, Joemar; Lacasan-Nagba, Junah (Universitas Negeri Semarang (UNNES) in cooperation with ACPES (ASEAN Council of Physical Education and Sport), 2023)
Adolescence is a common experience for adolescents worldwide, preparing them for the future and developing academic performance. In the Philippines, increasing educational accountability and the No Child Left Behind Act have reduced physical education classes, affecting students' fitness and cognitive development. Physical fitness plays a crucial role in academic performance, as it increases blood flow, oxygen extraction, and pulmonary ventilation. Improved cardiorespiratory fitness reduces depression, anxiety, and self-esteem, leading to better academic performance. Play is essential for learning, and physical activity improves the cardiovascular, vascular, metabolic, endocrine, and immune systems. Adolescent sedentary lifestyles, caused by gadgets, can lead to poor academic performance. Hence, the purpose of this study is to examine the relationship between students' physical fitness levels and academic performance in Senior High School students officially enrolled in S.Y 2022-2023.